REFORMULASI INOVASI KURIKULUM: KAJIAN LIFE SKILL UNTUK MENGANTARKAN PESERTA DIDIK MENJADI WARGA NEGARA YANG SUKSES - Rohmalina Wahab (Ta'dib: Jurnal Pendidikan Islam, 2012)
Life skill oriented education for students is a provision in facing andsolving life's problems, wether as an independent personal life,as member of community, and as a citizen. There are four types of life skills that must beowned by the individual; the personal skills, social skills, academic skills, and vocational skills. The efforts to reformulate life skill education is by presentinglearning package which is presented in a limited and open according to the needsand potential of local resources, wether in business activities in agriculture,aquaculture farms, plantations, fisheries and agricultural production,domestic industry, or other types of activity , in which participants learnif curriculum provided is less able to fulfill the needs, can add, subtract and evenchange itself according to desired needs. Life skills education should beimplemented in accordance with the objectives, functions and benefits of lifeskills to create an individual to be able to face life independently.